Influence of thermal exposure on microstructural stability and tensile properties of a new Ni-base superalloy - Hao Liu; Xinbao Zhao; Yong Yuan; Yingying Dang; Weiqi Li; Jiachen Xu; Yuan Cheng; Quanzhao Yue; Yuefeng Gu; Ze Zhang (Journal of Materials Research and Technology, 2022)
The influence of long-term thermal exposure on microstructure evolution and tensile behavior of a new wrought γ′-hardened Ni-base superalloy at different temperatures are investigated. The experimental superalloys are thermal exposure at 650 °C for different times up to 2300 h and tensile tests are performed in both heat treatment and thermal exposure conditions. The results show that some discontinuous carbides precipitate at the grain boundaries and spherical γ′ precipitates homogeneously disperse within the γ matrix after heat treatment. During thermal exposure, the γ′ precipitates remain spherical morphology, and the coarsening behavior of γ′ conforms to the LSW model. The tensile strength of the experimental superalloy after heat treatment generally shows a downward trend with the increase of tensile temperature while the elongation reaches a maximum at 650 °C. After thermal exposure, the tensile strength of the experimental superalloy has improved while the elongation slightly decreases.